A broad range of organophosphate tri- and di-esters in house dust from Adelaide, South Australia: Concentrations, compositions, and human exposure risks. (September 2020) - Huang, Yichao; Tan, Hongli; Li, Liangzhong; Yang, Liu; Sun, Fengjiang; Li, Jing; Gong, Xue; Chen, Da
Highlights: Ubiquitous presence of a suite of tri- & di-OPEs discovered in Adelaide house dust. TPHP-based OPEs emerged in house dust with combined levels surpassing that of TPHP. Di-OPEs constituted ~13% of total tri-OPE concentrations in Adelaide house dust. The complexity of the OPE group raises concern on potential human exposure risks. Abstract: This study aimed to investigate the occurrences of a suite of thirty-one organophosphate tri-esters (tri-OPEs) and six di-esters (di-OPEs) in house dust collected from Adelaide, South Australia. The results demonstrate ubiquitous presence of most OPEs in Adelaide house dust, with median concentration of 40, 200 and 5260 ng/g dry weight for ∑tri-OPEs and ∑di-OPEs, respectively. A number of emerging OPEs with chemical structures resembling that of triphenyl phosphate (TPHP), including bisphenol A bis(diphenyl phosphate) (BPA-BDPP), cresyl diphenyl phosphate (CDP), isodecyl diphenyl phosphate (IDDPP), resorcinol-bis(diphenyl)- phosphate (RDP), as well as a suite of isopropylated or tert -butylated triarylphosphate ester isomers (ITPs or TBPPs), were frequently detected with combined levels surpassing that of TPHP. The investigated di-OPEs, predominated by DPHP, consisted of approximately 13% of the ∑tri-OPEs concentrations. Median concentration ratios of diphenyl phosphate (DPHP) and bis(2-ethylhexyl) phosphate (BEHP) to their respective tri-OPEs [i.e., TPHP and tris(2-ethylhexyl) phosphate (TEHP)] were determined to be 1.8 and 2.0, respectively, indicating possible commercial applications for these two di-OPEs. The estimated human intakes of dust-associated OPEs via dust ingestion and dermal contact were much lower than the reference doses. However, the risks of human exposure to OEPs may be complicated by quickly expanding family of OPEs containing various analogues and isomers as well as additional exposure pathways. Therefore, elucidation of human exposure to OPEs and associated risks requires extensive efforts in analytical, environmental, toxicological, and epidemiological investigations.